Is Charity a Choice? Protestant Evangelicals, Charitable Choice and the Feeding of the Poor. - Ronald Eric Matthews, Jr.; Lane, Janet (Newcastle upon Tyne : Cambridge Scholars Pub., 2012)
Debates on public policy in the United States are shaped, in part, by moral and religious commitments of individuals and communities. Heclo (2003) writes in Religion Returns to the Public Square, "Government policy and religious matters ... both claim to give authoritative answers to important questions about how people should live." Heclo's words apply especially to the issue of poverty and welfare reform, a matter on which the great religious traditions have played an integral part. Apar ...
TABLE OF CONTENTS; LIST OF FIGURES; LIST OF TABLES; PREFACE; ACKNOWLEDGEMENTS; CHAPTER ONE; CHAPTER TWO; CHAPTER THREE; CHAPTER FOUR; CHAPTER FIVE; CHAPTER SIX; CHAPTER SEVEN; APPENDIX 1; APPENDIX 2; NOTES; WORKS CITED.
Description based on print version record.
Keywords: Charity -- Ethics -- Religion; Community development -- Religious aspects; Social service -- Religious aspects; Church charities -- United States; Welfare state -- United States; Church and state -- United States; RELIGION / Christianity / General; RELIGION / Ethics; Electronic books